2004
DOI: 10.1086/381578
|View full text |Cite
|
Sign up to set email alerts
|

FoodNet Estimate of the Burden of Illness Caused by NontyphoidalSalmonellaInfections in the United States

Abstract: To determine the burden of Salmonella infections in the United States, Foodborne Diseases Active Surveillance Network (FoodNet) investigators conducted population-based active surveillance for culture-confirmed Salmonella infections during 1996-1999 at FoodNet laboratories. In addition, all clinical microbiology FoodNet laboratories were surveyed to determine their practices for isolating Salmonella. Telephone interviews were also conducted among residents of the FoodNet sites to determine the proportion of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
350
1
12

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 557 publications
(375 citation statements)
references
References 40 publications
6
350
1
12
Order By: Relevance
“…Other authors have previously reported similar studies to reconstruct the surveillance pyramid for specific pathogens or for gastrointestinal illness in general [1,9,[11][12][13]33]. The current study is more comprehensive than previous studies, considering seven enteric pathogens in seven countries.…”
Section: Comparison With Other Reconstruction Studiesmentioning
confidence: 94%
“…Other authors have previously reported similar studies to reconstruct the surveillance pyramid for specific pathogens or for gastrointestinal illness in general [1,9,[11][12][13]33]. The current study is more comprehensive than previous studies, considering seven enteric pathogens in seven countries.…”
Section: Comparison With Other Reconstruction Studiesmentioning
confidence: 94%
“…Salmonella is a pathogen that causes human food-borne illness worldwide, infects both mammalian intestinal epithelial cells and macrophages, and has an increased propensity to cause invasive, extra-intestinal disease in the elderly (1,13). In C. elegans, S. typhimurium establishes persistent infection in the intestinal lumen but does not replicate inside intestinal epithelial cells (14,15), suggesting that host defense mechanisms to combat Salmonella infection may be more successful in nematode than in mammalian cells.…”
mentioning
confidence: 99%
“…Formal surveillance networks were established with the aim of demonstrating the burden of enteric diseases in the developed world, focusing on sporadic disease (Scallan and Angulo, 2007a,b;Kirk et al, 2008;PHAC, 2008;Majowicz et al, 2010). These surveillance networks facilitated landmark research studies into sporadic enteric disease Tam et al, 2003, de Wit 2001, Voetsch et al, 2004Jones et al, 2006a). Many of these surveillance systems have provided population-based platforms for case-control studies.…”
Section: Insights Gained From 20 Years Of Investigations Of Sporadic mentioning
confidence: 99%